(Re) construction of historical memory: identity and urban re-valuation of the first Diagonal in Chile. (2022)
In the process of urban regeneration, the re-valuation of public space and the elements that configure it assume the potential in the regeneration process, integrating elements as the basis components in the consolidation of urban dynamics. Also, the contained memory of the city, understood as public inheritance, is a continuous and participatory process in which we construct the sense of belonging and place. The (re) construction of historical memory of the Avenue Diagonal Pedro Aguirre Cerda, the first diagonal axis of Chile, has partly defined the structure of the landscape of the city of Concepcion, being a container of social, historical, and natural processes that accidentally occurred. Unfortunate but ideal scenarios have been the successive earthquakes that have made our country a fertile ground for rethinking and materializing ideas. It is, in the post-1939 earthquake, when the reconstruction permitted revolutionary thoughts coming from modern Europe and that were materialized, with a privileged location in both the historical space and in the physical city. The appearance of this axis, in the apposition of the foundational Damero’s plane, is an innovative project that breaks this historic urban trend, taking into Chile, and more specifically into Concepción, a chance to expound innovative ideas, aimed to change the urban landscape prevailing at that time. In terms of spatial configuration, this diagonal axis is a superposition of historical layers in their development and materialization that has become a mass of history and that is still in development. In other words, it is dynamic and open, consolidating it periodically as an identity space city landscape, harmoniously uniting both the civic world represented by the square courts with the academics symbolized in the University of Concepción. It is proposed to unravel and rescue the historical context that adds a value in the configuration and coordination of the various parties in relation to the on-going transformation and constitution of this urban piece and its constant identity re-evaluation in favor of the regeneration processes.